2020
DOI: 10.1002/ijc.33250
|View full text |Cite
|
Sign up to set email alerts
|

Dual staining for p16/Ki‐67 to detect high‐grade cervical lesions: Results from the Screening Triage Ascertaining Intraepithelial Neoplasia by Immunostain Testing study

Abstract: We compared clinical performance of p16/Ki-67 dual-stained cytology and human papillomavirus (HPV) genotyping, via different algorithms-alone, or in combination with cytology-to identify cervical intraepithelial neoplasia grade 2 or worse (CIN2+) and grade 3 or worse (CIN3+) in women referred to as colposcopy. We included 492 cervical specimens (134 normal, 130 CIN1, 99 CIN2, 121 CIN3, 8 cancers) randomly selected from 1158 specimens with valid conventional cytology, HPV (cobas 4800 HPV test) and biopsy result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The significantly higher specificity of CINtec PLUS than HPV test was consistently observed, and in this respect, we note that CINtec PLUS is currently approved for triaging those testing positive in HPV primary screening [ 29 ]. The lower sensitivity, albeit with the caveats noted, and higher specificity of CINtec PLUS compared to HPV test we observed is consistent with a screening triage study recently reported in a Canadian population [ 23 ] and many other studies [ 17 , 21 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significantly higher specificity of CINtec PLUS than HPV test was consistently observed, and in this respect, we note that CINtec PLUS is currently approved for triaging those testing positive in HPV primary screening [ 29 ]. The lower sensitivity, albeit with the caveats noted, and higher specificity of CINtec PLUS compared to HPV test we observed is consistent with a screening triage study recently reported in a Canadian population [ 23 ] and many other studies [ 17 , 21 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…CINtec PLUS has been shown to be more sensitive than cytology with equal specificity, and more specific than HPV testing with relatively comparable sensitivity for detecting cervical intraepithelial neoplasia grade 2 or worse (CIN2 ) in LSILs [ 11 , 17 , 18 , 19 , 20 ]. While the clinical applications of CINtec PLUS in LSIL triage have been assessed in several studies in Europe and elsewhere [ 11 , 18 , 21 , 22 ], there has been limited evaluation of this method to serve as an adjunct test in LSIL triage in North American settings [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For miRNA (miR-9) assay, three studies recorded sensitivity, specificity and area under the ROC curve ranges of 52.9-67.3%, 76.4-94.4%%, and 0.71-0.85, respectively based on RT-qPCR platform using serum and tissue samples [2,11,53], with77.8% PPV and 70.2% NPV reported by Park et al [11]. 3) For the p16INK4a / ki-67 assays, twenty studies included reported sensitivity, specificity, PPV, NPV, and AUC ranges of 50-100%, 39-90.4%, 11.1-92.3%, 86.7-100%, and 0.76-0.90, respectively, based on immunocytochemistry (ICC) platform using liquid based cytology (LBC) samples [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . On the other hand, four studies evaluating Vascular Endothelial Growth Factor (VEGF) assay reported sensitivity, specificity, and AUC ranges of 56-83.5%, 74.6-96%, and 0.83-0.88, respectively, based on Elisa platform using serum [5,[50][51][52], with Lawicki et al being the only author who reported PPV and NPV at 86 and 82%, respectively.…”
Section: Diagnostic Performance Of the Listed Assays To Detect Cin2+mentioning
confidence: 99%
“…p16/Ki-67 IHC has been used most frequently throughout the studies. Similar to p16 and Ki-67 IHC alone, an increase in the number of DS-positive biopsy specimens was correlated with a more severe histological diagnosis [ 32 , 41 , 42 , 43 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and with HPV DNA positivity [ 41 , 42 , 43 , 58 , 59 , 63 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 69%
“…p16/Ki-67 IHC has been used most frequently throughout the studies. Similar to p16 and Ki-67 IHC alone, an increase in the number of DS-positive biopsy specimens was correlated with a more severe histological diagnosis [32,[41][42][43][53][54][55][56][57][58][59][60][61][62][63] and with HPV DNA positivity [41][42][43]58,59,63] (Table 2). Ki-67 was generally expressed in combination with p16 IHC, as DS positivity.…”
Section: Resultsmentioning
confidence: 75%